Association between insulin‐like growth factor‐1 and systolic blood pressure in children and adolescents with short stature. Issue 6 (1st April 2021) - Zhao, Qianqian; Zhang, Mei; Chu, Yuntian; Sun, Hailing; Ban, Bo
Abstract: The relationship between insulin‐like growth factor‐1 (IGF‐1) and systolic blood pressure (SBP) is controversial in adults and children. The purpose of this study was to investigate the relationship between the IGF‐1 standard deviation score (IGF‐1 SDS) and SBP in children with short stature. A cross‐sectional analysis including 1315 children with short stature was conducted from March 2013 to October 2020. We estimated IGF‐1, blood pressure and other laboratory tests, and anthropometric indicators were also evaluated. Subgroup analyses of the pubertal stage, sex, growth hormone levels, thyroid hormone levels, fasting blood glucose levels, and triglyceride levels were performed. A positive association between the IGF‐1 SDS and SBP was observed by univariate analysis ( p < .001). We further found a nonlinear association between the IGF‐1 SDS and SBP. The inflection point for the curve was found at an IGF‐1 SDS level of −2.91. In multivariate piecewise linear regression, there was a positive association between the IGF‐1 SDS and SBP when the IGF‐1 SDS was greater than −2.91 ( β 1.56, 95% CI: 0.91, 2.22; p < .001). However, we did not observe a significant relationship between the IGF‐1 SDS and SBP when the IGF‐1 SDS level was less than −2.91 ( β −0.95, 95% CI −3.17, 1.28; p = .379). This association was consistent across subgroup analyses. The present study demonstrated that there is a nonlinear relationship between the IGF‐1 SDS and SBP in children with short stature. Increased serum IGF‐1 levels were associated with elevated SBP when the IGF‐1 levels reached the inflection point.